The Oretical Methodology for Risk Reduction - Timofeeva, Svetlana Semyonovna; Nabievich, Musaev Marufdzhan; Azimzhonovich, Boboev Azizzhon; Azimjonovna, Boboeva Farangiz (European Journal of Life Safety and Stability (2660-9630), 2022)
It is extremely important to always identify, create and follow the same methodology for risk analysis and mitigation, as this reduces the likelihood of misjudgment and forgetfulness. The presence of a kind of checklist, which lists all the steps that must be performed for a correct and complete assessment and risk reduction, allows you to apply the same methodology to all analyzed cases, being able to compare and analyze them systematically.